The emerging role of circulating microRNAs as biomarkers in autoimmune diseases. (November 2014) - Zeng, Li; Cui, Juncheng; Wu, Haijing; Lu, Qianjin
Abstract The highly conserved RNAs known as microRNAs (miRNAs) are a class of small, single-stranded, non-coding RNAs that play a critical role in the regulation of host genome expression at the posttranscriptional level. MiRNA-mediated gene regulation is vital for normal cellular functions, such as the cell differentiation, proliferation and apoptosis, and nearly one-third of human messenger RNAs might be miRNA targets. Increasing evidence has suggested that miRNAs play a critical role in the regulating the immune system and preventing autoimmune disorders. Circulating miRNAs, which can be easily detected by a non-invasive methods, have been proven to be able to distinguish diseased individuals from healthy subjects. In addition, these circulating miRNAs have relatively high sensitivity and specificity and thus have been developed as biomarkers for the diagnosis and monitoring of human diseases. To date, nearly 100 circulating miRNAs have been proven to be biomarkers for various diseases, and this number continues to rise. This review aims to summarize the most promising identified circulating miRNAs as potential biomarkers in autoimmune diseases and to discuss current challenges and future directions in the field.